2013
DOI: 10.1021/jf404100x
|View full text |Cite
|
Sign up to set email alerts
|

Effective Extraction Method for Determination of Neonicotinoid Residues in Tea

Abstract: Sample preparation using an absorbent for removal of polyphenols and a solid-phase extraction (SPE) cartridge for cleanup followed by high-performance liquid chromatography (HPLC) has been investigated for the simultaneous determination of eight neonicotinoid insecticides (dinotefuran, nitenpyram, thiamethoxam, imidacloprid, clothianidin, imidaclothiz, acetamiprid, and thiacloprid). After tea samples were soaked with water and extracted with acetonitrile, sample extracts were treated with an appropriate amount… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 22 publications
(45 reference statements)
0
34
0
Order By: Relevance
“…In this paper, these absorbents were tested in combination with the inexpensive and excellent absorbent PVPP, which has been used to eliminate polyphenols from tea samples. 3 In order to save the more expensive absorbents PSA and GCB, different amounts of PVPP were rst added to eliminate polyphenols, which cause the main disturbance in the tea extract. Spiked tea samples (0.05 mg kg À1 ) were soaked in water and extracted with ACN.…”
Section: Extraction Solvent Selection and Evaluation Of Cleanupmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper, these absorbents were tested in combination with the inexpensive and excellent absorbent PVPP, which has been used to eliminate polyphenols from tea samples. 3 In order to save the more expensive absorbents PSA and GCB, different amounts of PVPP were rst added to eliminate polyphenols, which cause the main disturbance in the tea extract. Spiked tea samples (0.05 mg kg À1 ) were soaked in water and extracted with ACN.…”
Section: Extraction Solvent Selection and Evaluation Of Cleanupmentioning
confidence: 99%
“…The LOQs were quite satisfactory when compared to the regulatory limits of daily exposure in tea. 3 Method accuracy and recovery were evaluated by the addition of standard solutions in blank (green, black and oolong) tea samples. Six aliquots of the tea matrix were spiked with target compounds at three concentration levels: 0.01, 0.05 and 0.5 mg kg À1 .…”
Section: Linearity Loq and Recoverymentioning
confidence: 99%
“…As shown in Fig.1 B, a good separation and reproducible chromatogram was achieved and 16 peaks were marked as the common peaks (from peak 1 to peak 16) in the chromatograms of the 33 raw herbs. Nine peaks (1,2,3,4,7,10,12,13,16) in the HPLC fingerprint profile were identified by comparing the UV spectra and retention time with the reference compounds. Peak 16 (linarin), the most important active constituents of CIF (China Pharmacopoeia Committee 2010), was chosen to calculate the relative retention time (RRT) and relative peak area (RPA) of all the other peaks.…”
Section: Hplc Fingerprint Analysismentioning
confidence: 99%
“…However, the limited availability of various chemical standard substances for quantitative analysis is a major hurdle [11]. On assessing the alternative measures available for the practical comprehensive determination of NDSs, the single standard of determination multiple components (SSDMC) method is worth considering [12,13].Through the above analysis, it is necessary to perform the method based on SSDMC method and fingerprint analysis in routine quality control of CIF. In the process, techniques such as HPLC [14], gas chromatography (GC) [15], high performance capillary electrophoresis (HPCE) [16], gas chromatography-mass spectrometry (GC-MS) [17] and liquid chromatography-mass spectrometry (LC-MS)…”
Section: Introductionmentioning
confidence: 99%
“…Different mobile phases, including methanol-water, acetonitrile-water, methanol-water with 0.1% formic acid and methanol-water with 0.01% formic acid, were investigated based on previous studies. [17][18][19][20] It was found that acetonitrile could provide better ionization conditions than methanol. Nevertheless, all of the peak shapes of compounds became abnormal with peak broadening when acetonitrile was used as an organic solvent.…”
Section: Optimization Of Uplc-ms/ms Conditionsmentioning
confidence: 99%